Analysis of the economic eﬃciency of antiparasitic treatments in sheep breeding in the Stavropol Territory - V. I. Kolesnikov (Российский паразитологический журнал, 2020)
The purpose of the research is to analyze the economic eﬃciency of planned antiparasitic deworming in sheep-breeding farms by the veterinary service of the region.Materials and methods. The studies were carried out using statistical data from the Veterinary Directorate of the Stavropol Territory for 2015-2019 and guidelines for determining the economic eﬃciency of antiparasitic measures. Economic losses were estimated at regional purchase prices for livestock products as of 2019. The calculations used indicators such as morbidity, mortality, and specific losses of the main product (meat, wool) per sick animal. The economic eﬃciency of veterinary measures for parasitic diseases of sheep was determined by the indicator of the prevented economic damage.Results and discussion. Analysis of the results of the treatment of sheep by the veterinary service of the region over a five-year period for the prevention of parasitic diseases showed that they annually carry out a large amount of antiparasitic treatments, but it should be noted that their number for all infestations decreased in 2019 compared to 2015 from 10180.0 thousand to 5231.0 thousand. Actual economic damage from parasitic diseases amounted to 10343.5 thousand rubles, and the amount of economic damage prevented as a result of planned deworming of sheep was 3.6 times higher than the amount of actual economic damage and amounted to 37895.7 thousand rubles.